Bear and fireweed painting on a building in Yellowknife, NWT ... - Campbell, Sandy (University of Alberta Library, 2015)
This painting of black bears in fireweed by Dean E. Robertson is on the side of a building on Franklin Avenue in Yellowknife. The painting is dated 2005. It is one of many paintings and murals that are on the exteriors of buildings in Yellowknife. ...